Artificial Intelligence Applications in Travel Technology and Financial Management Systems - Kingsley Ugonna Muolokwu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of artificial intelligence (AI) within travel technology (TravelTech) and financial management systems (FinTech) is reshaping the global service ecosystem through automation, personalization, and predictive intelligence. This review explores the convergence of these two sectors, highlighting how AI enables intelligent travel planning, dynamic pricing, fraud detection, and automated financial processes. The study examines the evolution of data-driven systems that leverage machine learning, natural language processing, and predictive analytics to improve customer experience, operational efficiency, and decision-making. It further discusses the convergence of AI-enabled payment systems, customer profiling, and loyalty management frameworks that link travel behavior with financial transactions, thereby fostering unified digital ecosystems. Ethical and regulatory challenges such as data privacy, algorithmic bias, and model governance are addressed, emphasizing the need for transparency and accountability in AI deployment. Emerging trends including generative AI, digital twins, and autonomous systems are identified as transformative forces driving innovation across TravelTech and FinTech. The review concludes that the strategic adoption of AI requires strong governance, interoperability, and cross-sector collaboration to ensure sustainable, ethical, and scalable integration. Ultimately, the study provides a comprehensive framework for understanding how AI-driven convergence enhances value creation, efficiency, and resilience within the interconnected domains of travel and finance.